2021
DOI: 10.1029/2021jc017511
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Centennial Subpolar North Atlantic Cooling Trend in the FGOALS‐g2 Historical Simulation

Abstract: A cold blob, manifested as a centennial cooling trend in sea surface temperature (SST), is observed in the mid‐latitude North Atlantic. The presence of the cold blob is hypothesized as an evidence of a slowdown of Atlantic Meridional Overturning Circulation (AMOC), based on paleoclimate proxies and global climate models (GCMs). However, the performance of GCMs in simulating the cold blob remains unsatisfactory in terms of the SST cooling rate and the spatial extent. This study investigates the forcing mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…4d vs a ). This is consistent with studies showing that T NA can be driven by external radiative forcing, or more general, the atmospheric forcing without an explicit role of AMOC change 21 , 22 , 48 , 49 . In contrast to T NA , the SSS indices show little response to volcanic and stratospheric ozone forcing (Fig.…”
Section: Resultssupporting
confidence: 92%
“…4d vs a ). This is consistent with studies showing that T NA can be driven by external radiative forcing, or more general, the atmospheric forcing without an explicit role of AMOC change 21 , 22 , 48 , 49 . In contrast to T NA , the SSS indices show little response to volcanic and stratospheric ozone forcing (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Although the observed North Atlantic cold blob extends further south to 40N, atmospheric forcing principally contributes to the northern portion of the cold blob, as the atmosphere-forced cooling is concentrated on the north of 50N, which is approximately the latitude of the inter-gyre boundary. SSTAs south of 50N are predominantly subject to the influence of changes in AMOCassociated ocean heat transport, as suggested by previous model studies (Keil et al 2020;Fan et al 2021). Additionally, the southward Ekman transport induced by strong surface westerlies over the inter-gyre boundary could spread the subpolar cooling anomalies further south.…”
Section: North Atlantic Ssta Trend In Response To 𝑄 Atmo Changementioning
confidence: 54%
“…The other argument is that the cold blob might not be a sole result of decreased northward ocean heat transport due to the AMOC decline. A model-based study suggests that the AMOC weakening contributes less than 30% of the cold blob in terms of its intensity and spatial extent (Fan et al 2021). In addition, the timing of the cold blob precedes the simulated AMOC decline (Drijfhout et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study 8 showed that the atmosphere can contribute approximately 50% of the observed cooling trend over the NAWH due to stronger local westerlies in response to external forcing that enhance heat loss from the ocean through turbulent heat fluxes. A past study 9 also indicated that cold blobs, equivalent to the NAWH, are due to reduced heat transport by surface turbulent heat fluxes and ocean currents, and that AMOC slowdowns make only a marginal contribution to cold blobs. These suggested various theories indicate that the mechanism of the NAWH formation by the warming climate is still under discussion.…”
Section: Introductionmentioning
confidence: 99%